IRONY AND CULTURAL CONCEPTS IN UZBEK SHORT PROSE: TAQDIR, OR-NAMUS AND ANDISHA AS COGNITIVE FOUNDATIONS OF IRONIC STRATEGIES - Kholbutaeva , Feruza (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The paper examines three key linguocultural concepts of the Uzbek language – taqdir, or-namus, and andisha – as cognitive foundations of irony in S. Vafo’s prose. It is shown that each concept generates a specific type of irony: taqdir gives rise to providential irony, or-namus to immanent irony, and andisha functions as a cultural prohibition against distancing from the norm. A comparison is drawn with N.A. Teffi’s ironic strategy, in whose texts analogous value domains possess no «immunity» to authorial deconstruction. The difference is described through the opposition «distance from the norm» (Russian tradition) vs «fusion with the norm» (Uzbek tradition).